World Statistics Pocketbook 2019 - United Nations (United Nations, 2019)
Over 50 indicators have been collected from more than 20 international statistical sources and are presented in one-page profiles for 30 world geographical regions and 232 countries or areas. The Pocketbook is organized into five sections; general information, economic indicators, major trading partners, social indicators, and environmental and infrastructure indicators. It presents data for the economic, social, environmental and infrastructure sections for three reference years - 2005, 2010 and 2019 - when available or the most recent data previous to these years, back to 2000, when it is not.